Contribution of universities health and safety services in achieving the sustainable development goals - M. Samper Rivas; C. Salcines; P. López-Roldán; S. Rosa; D. Monge Martín; E. Colino (Frontiers in Public Health)
IntroductionUniversities play a pivotal role in advancing the Sustainable Development Goals (SDGs) and the 2030 Agenda through their educational mission, research activities, and contributions to social well-being, economic progress, and social cohesion. Beyond their conventional functions, universities can contribute to sustainability through the specific actions of their Occupational Health and Safety (OHS) services. This study explores the contribution of university OHS services to the achievement of the SDGs within the Spanish higher education system.MethodsA cross-sectional survey was conducted among Spanish universities to identify OHS actions linked to the SDGs and to assess their institutional impact. The study presents a structured methodology that classifies OHS actions into specific and general categories, mapped across three strategic dimensions: person, environment, and culture.ResultsResults reveal that OHS services contribute to a wide range of SDGs, extending beyond the traditionally recognized SDG 3 (Good Health and Well-being) and SDG 8 (Decent Work and Economic Growth).DiscussionThis research provides an original SDG Impact Matrix that highlights the multidimensional role of OHS services in fostering sustainability within universities. The findings offer valuable insights for integrating OHS strategies into institutional sustainability policies and expanding their role as active agents in the advancement of the 2030 Agenda.